METODE DAN PROSEDUR PENERJEMAHAN MANUAL BOOK KAMERA SUBBAB INSTRUKSI KESELAMATAN - Utami, Feradita Rizki; Aibonotika, Arza; Nasution, Yenny Aristia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The purpose of this research is to find translation method andprocedure from manual book camera. Using Newmark Translation Theories thatseparating method by 2 cathegory. 1 the method that emphasis on source language and2 the one that emphasis on target language. The procedure is to search an effective wayto find the ringht and acceptable equivalent in target language from manual bookcamera. Focusing on security note for users by deviding source language and translatelanguage. Descripiting method and procedure used in the proses of translatinginstruction manual in manual book.Key Words: Translation, Method and Procedure, Security Note for Users, Descripting